Secondary Structure of Human De Novo Evolved Gene Product NCYM Analyzed by Vacuum-Ultraviolet Circular Dichroism - Matsuo, Tatsuhito; Nakatani, Kazuma; Setoguchi, Taiki; Matsuo, Koichi; Tamada, Taro; Suenaga, Yusuke (Frontiers in Oncology, 2021)
NCYM, a cis-antisense gene of MYCN, encodes a Homininae-specific protein that promotes the aggressiveness of human tumors. Newly evolved genes from non-genic regions are known as de novo genes, and NCYM was the first de novo gene whose oncogenic functions were validated in vivo. Targeting NCYM using drugs is a potential strategy for cancer therapy; however, the NCYM structure must be determined before drug design. In this study, we employed vacuum-ultraviolet circular dichroism to evaluate the secondary structure of NCYM. The SUMO-tagged NCYM and the isolated SUMO tag in both hydrogenated and perdeuterated forms were synthesized and purified in a cell-free in vitro system, and vacuum-ultraviolet circular dichroism spectra were measured. Significant differences between the tagged NCYM and the isolated tag were evident in the wavelength range of 190–240 nm. The circular dichroism spectral data combined with a neural network system enabled to predict the secondary structure of NCYM at the amino acid level. The 129-residue tag consists of α-helices (approximately 14%) and β-strands (approximately 29%), which corresponded to the values calculated from the atomic structure of the tag. The 238-residue tagged NCYM contained approximately 17% α-helices and 27% β-strands. The location of the secondary structure predicted using the neural network revealed that these secondary structures were enriched in the Homininae-specific region of NCYM. Deuteration of NCYM altered the secondary structure at D90 from an α-helix to another structure other than α-helix and β-strand although this change was within the experimental error range. All four nonsynonymous single-nucleotide polymorphisms (SNPs) in human populations were in this region, and the amino acid alteration in SNP N52S enhanced Myc-nick production. The D90N mutation in NCYM promoted NCYM-mediated MYCN stabilization. Our results reveal the secondary structure of NCYM and demonstrated that the Homininae-specific domain of NCYM is responsible for MYCN stabilization.